Kerala Tourism At a Glance - Smitha Das (Marketing Mastermind 2009, 2009)
This article provides an overview of Kerala's tourism industry and explains the developmental initiatives taken by the state to showcase tourism products like ayurveda, backwaters, festivals, etc., as well as to market Kerala Tourism as a super brand. It explains marketing and advertising strategies adopted by the state with the intention of emerging as a preeminent tourism destination in the world. It concludes with the impact of tourism on the state's economy, threats faced by the tourism industry in the state and the expectations and prospects for the future.